OPTIMIZING THE GROWTH AND DEVELOPMENT OF TODDLERS THROUGH EMPOWERING CADRES AND MOTHERS OF TODDLERS WITH ASIKIA ACTIVITIES - Yuliawati, Dwi; Sheilla Tania Marcelina (Universitas Airlangga, 2024)
The toddler period is a vulnerable time, especially with regard to growth, as it can affect the development of children in the future. Therefore, it is necessary to intervene to increase the interaction of health professionals with parents to have a positive impact on child development. The Maternal and Child Health Information Sharing Agenda (ASIKIA) is an activity carried out in an effort to empower the community, especially cadres and mothers of toddlers in optimizing the growth and development of infants and toddlers. Community empowerment activities were carried out through cadre mentoring activities on March 14, 2023 and toddler mother class activities on March 16, 2023. The empowerment model used is Unlimited Totality Health Empowerement (UTHE) which uses several kinds of models in activities in the form of lectures, group discussions, demonstrations and discussions. The activities carried out proved to be able to increase the knowledge of cadres about stimulation of growth and development of toddlers as shown by the results of the pre-test and post-test where before being given counseling, cadre knowledge in the good category was 50% and after being given counseling cadre knowledge increased to the good category as much as 88%. Likewise, the knowledge of mothers of toddlers about stunting showed results before being given counseling, the knowledge of mothers of toddlers in the good category was 17% and after being given counseling, the knowledge of mothers of toddlers increased to the good category by 100%. In addition, the success of the activity is also indicated by the ability of cadres to correctly assess child development using the